PENGARUH INTENSITAS PEER GROUP COMMUNICATION DAN PENGENDALIAN DIRI TERHADAP TINGKAT KECANDUAN GAME ONLINE MOBILE LEGENDS:BANG BANG DI KALANGAN GENERASI Z - Nadhif Zufar Faizal, Sulthan; Surayya Ulfa, Nurist; Naryoso, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Generation Z is the largest age group in Indonesia, accounting for approximately 27.94 percent of the total population. Online gaming has become an integral part of daily life for Generation Z in Indonesia. As a generation raised in the digital era, Generation Z shows a strong attachment to technology, including online games, which, when played with high intensity, can lead to addiction. One of the most popular online games among Generation Z is Mobile Legends. This study aims to examine the influence of peer group communication intensity and self-control on the level of addiction to Mobile Legends among Generation Z. The study employs a quantitative explanatory method with purposive sampling involving 108 respondents. The results indicate that peer group communication intensity has a significant effect on the level of online gaming addiction, where higher communication intensity within peer groups correlates with a greater likelihood of addiction. On the other hand, low self control also significantly contributes to higher levels of online gaming addiction, especially in Mobile Legends